Implementation of Executive Information Systems in Decision Making in the Development of Branch Leadership Organizations of IPNU-IPPNU Pretek Central Java - Budi Nugraha; Hopinatun Napiah; Khafidzin Khafidzin; Fina Syafaah; Edi Saputra (JCIC : Jurnal CIC Lembaga Riset dan Konsultan Sosial, 2021)
Executive information system (EIS) is defined as a computer-based information system designed to provide executives with internal and external information that is easily accessible and relevant to management activities. The application of EIS in companies or organizations is expected to be able to help the work of leaders in making the right decisions. One of them in the development of branch leadership organizations of IPNU-IPPNU Pretek. This organization is a community organization under the auspices of Nahdlatul Ulama. Members of the student age where the state of environmental conditions and human resources that are still not considered important to technological developments. In order to maximize the role of the management information system. Members must jointly learn about the management information system. So that future activities facilitate work and can support the taking of executive holders.